AUTHORITY AND LEGAL CONSEQUENCES OF CITY GOVERNMENTS IN FULFILLING SUSTAINABLE ECO-CITIES: A STUDY ON GREEN OPEN SPACE PROVISION - Charles Godang Halomoan Hasibuan; Iza Rumesten RS; Suci Flambonita (Lex LATA, 2026)
Environmental issues in urban areas are becoming increasingly complex due to rising population density and ecological degradation. Providing Green Open Space (RTH) with a minimum threshold of 30% of the total urban area is a statutory obligation, yet its implementation is frequently neglected due to weak legal enforcement. This normative juridical research aims to analyze the implementation of city government authority in green open space development and the legal consequences that arise when such obligations are unfulfilled. Utilizing statute, case, and futuristic approaches, the study concludes that city governments possess full, attributive authority under Law Number 26 of 2007 concerning Spatial Planning to plan and control green spaces based on ecoregions. Non-compliance or negligence by the city government in providing green open spaces results in legal consequences, specifically granting citizens the legal standing to file lawsuits (citizen lawsuits or class actions) for violations of human rights to a healthy environment. Furthermore, it triggers administrative and judicial sanctions in accordance with the Environmental Protection and Management Law. This study recommends strengthening the legal commitment of city governments to integrate eco-city concepts to realize sustainable development goals.